Randomized Trial of Radiotherapy Versus Transoral Robotic Surgery for Oropharyngeal Squamous Cell Carcinoma: Long-Term Results of the ORATOR Trial. Issue 8 (10th March 2022) - Nichols, Anthony C.; Theurer, Julie; Prisman, Eitan; Read, Nancy; Berthelet, Eric; Tran, Eric; Fung, Kevin; de Almeida, John R.; Bayley, Andrew; Goldstein, David P.; Hier, Michael; Sultanem, Khalil; et al.
Abstract : PURPOSE: The incidence of oropharyngeal squamous cell carcinoma (OPSCC) has risen rapidly, because of an epidemic of human papillomavirus infection. The optimal management of early-stage OPSCC with surgery or radiation continues to be a clinical controversy. Long-term randomized data comparing these paradigms are lacking. METHODS: We randomly assigned patients with T1-T2, N0-2 (≤ 4 cm) OPSCC to radiotherapy (RT) (with chemotherapy if N1-2) versus transoral robotic surgery plus neck dissection (TORS + ND) (with or without adjuvant therapy). The primary end point was swallowing quality of life (QOL) at 1-year using the MD Anderson Dysphagia Inventory. Secondary end points included adverse events, other QOL outcomes, overall survival, and progression-free survival. All analyses were intention-to-treat. Herein, we present long-term outcomes from the trial. RESULTS: Sixty-eight patients were randomly assigned (n = 34 per arm) between August 10, 2012, and June 9, 2017. Median follow-up was 45 months. Longitudinal MD Anderson Dysphagia Inventory analyses demonstrated statistical superiority of RT arm over time ( P = .049), although the differences beyond 1 year were of smaller magnitude than at the 1-year timepoint (year 2: 86.0 ± 13.5 in the RT arm v 84.8 ± 12.5 in the TORS + ND arm, P = .74; year 3: 88.9 ± 11.3 v 83.3 ± 13.9, P = .12). These differences did not meet the threshold to qualify as a clinically meaningful change at any timepoint. Certain differences in QOL concerns including more pain and dental concerns in the TORS + ND arm seen at 1 year resolved at 2 and 3 years; however, TORS patients started to use more nutritional supplements at 3 years ( P = .015). Dry mouth scores were higher in RT patients over time ( P = .041). CONCLUSION: On longitudinal analysis, the swallowing QOL difference between primary RT and TORS + ND approaches persists but decreases over time. Patients with OPSCC should be informed about the pros and cons of both treatment options (ClinicalTrials.gov identifier: NCT01590355 ).